The Study of Food Security in the Special Region of Yogyakarta, Indonesia - Rika Harini; Irwansyah Sukri; Rina Dwi Ariani; Elya Pratiwi Isti Faroh; Hayyun Nadia; Utia Kafafa (Universitas Muhammadiyah Surakarta, 2021)
Food security is a burden to realize sustainable development in achieving the zerohunger goal. This study aimed to examine the distribution of food security levels and the factors that influence the level of food security in the Special Region of Yogyakarta. Quantitative analysis was carried out in this study based on secondary data. The method of determining food security was carried out by applying the concept of the Food Security and Vulnerability Atlas (FSVA) which consists of three food pillars, namely food availability, access, and utilization. The results proved that Gunungkidul Regency was the area with the highest score for food availability, while the lowest were Bantul and Sleman. On the pillars of food access and food utilization, the highest was in Sleman, while the lowest was in Gunungkidul. The value of food security from the highest were the City of Yogyakarta (84.47), Sleman Regency (82.37), Bantul (79, 51), Gunungkidul (79.31), and Kulon Progo (79.03). All areas in DIY are included in very good food security. Food security policies need to be directed at handling food-poor households in villages through increasing knowledge about nutrition. Meanwhile in urban areas, it can be done through expanding job opportunities and community empowerment.